Molecular Characterization of Candida parapsilosis by Microsatellite Typing and Emergence of Clonal Antifungal Drug Resistant Strains in a Multicenter Surveillance in China - Zhang, Li; Yu, Shu-Ying; Chen, Sharon C.-A.; Xiao, Meng; Kong, Fanrong; Wang, He; Ning, Ya-Ting; Lu, Min-Ya; Sun, Tian-Shu; Hou, Xin; Zhou, Meng-Lan; Kang, Wei; et al. (Frontiers in Microbiology, 2020)
Candida parapsilosis is an important species causing invasive candidiasis (IC) in China. The present survey was a national multicenter study of the molecular epidemiology and antifungal susceptibility profiles of C. parapsilosis. Non-duplicate C. parapsilosis isolates were collected from 10 hospitals across China in the CHIF-NET program 2016-17. Isolates were genotyped using four highly polymorphic microsatellite markers, and susceptibility profiles determined using Sensititre YeastOneTM YO10. A total of 319 C. parapsilosis from separate patients with IC were studied; 49.2%, 17.9%, and 10.3% isolates were from patients in surgical departments, general intensive care units (ICUs) and neonatal ICUs (NICU), respectively. C. parapsilosis showed good susceptibility to nine antifungal drugs. Microsatellite analysis identified 122 microsatellite (MT) types. Most MT types had sporadic distribution. However we identified 32 clusters across 10 hospitals; seven clusters were caused by seven endemic genotypes involving five or more isolates in hospitals designated as H01, H02, H06, and H10. These clusters mainly affected surgical departments and ICUs, except for genotype MT42 which was seen in 22 patients from NICU (hospital H06). Of 16 fluconazole-resistant isolates, seven from hospital H02 shared the same genotype MT70, and three from hospital H04 were of genotype MT47. For 37 isolates with non-wild type MICs to 5-flucytosine, 29 were from hospital H01 (genotype MT48). Here we present the first nationwide molecular epidemiology study of C. parapsilosis in China, identified several previously unrecognized clusters, which included antifungal drug resistant isolates. These findings provide important data for control of IC in China.